Unceasing strife, unending fear : Jacques de Thérines and the freedom of the church in the age of the last Capetians - Jordan, William Chester, 1948- (Princeton University Press, 2005)
This absorbing book explores the tensions within the Roman Catholic church and between the church and royal authority in France in the crucial period 1290-1321. During this time the crown tried to force churchmen to accept policies many considered inconsistent with ecclesiastical freedom and traditions--such as paying war taxes and expelling the Jews from the kingdom. William Jordan considers these issues through the eyes of one of the most important and courageous actors, the Cistercian monk, professor, abbot, and polemical writer Jacques de Thérines. The result is a fresh perspective on wha.